Work-Life Balance and Time Management on Academic Achievement of Part-Time Students in Yogyakarta: Testing Social Support as a Moderator - Soares, Luis Americo; Zahra, Zulfa Putri Az-; Miswanto; Biyanto, Frasto; Siregar, Baldric; Ximenes, Antonio (Dinasti Publisher, 2025)
This study aims to investigate the impact of work-life balance and time management on the academic achievement of part-time university students in Yogyakarta, with social support as a moderating variable. The research addresses the growing challenge faced by students managing both academic and professional responsibilities. A quantitative approach was applied using a survey of 155 purposively selected part-time students. Validated instruments measured work-life balance, time management, academic achievement, and social support. Moderated regression analysis (MRA) in SPSS revealed that the final model accounted for 98.4% of the variance in academic achievement (R2 = 0.984). Both work-life balance (? = -0.292, p < 0.001) and time management (? = -0.344, p < 0.001) had significant negative effects. However, social support positively moderated both relationships, reducing their negative impact (interaction effects: ? = 0.926 and ? = 0.880, respectively). The finding emphasizes the importance of institutional support and training to help students manage dual roles effectively.